Comparative Analysis of Bird Nest Wallet Production Quality In Rural and Urban Areas on Lombok Island - Nurul Imam Muzakir; Budi Indarsi; Soekardono Soekardono (International Forum of Researchers and Lecturers, 2025)
This study analyses the production and quality of nest Bird swallows (SBW) in rural and urban areas of Lombok Island, as well as the level of income of SBW breeders. Survey and purposive sampling techniques: this study involved 20 respondents, 10 of each rural and urban. Data was collected through interviews, observation field, and documentation, then explained in a way. Research results show that SBW production and quality in urban areas are taller compared to rural areas, supported by policies and modern technology such as the arrangement of temperature and humidity. Total production in urban areas reached 55,25 kg, while in rural areas, it was 23,8 kg. Feed becomes the primary determinant of This difference. In rural areas, constraints such as predator disturbance and dependence on natural conditions influence production results. Meanwhile​, quality urban nests​ are superior. This research provides recommendations for improving the management of SBW cultivation in rural areas through technology transfer, training, and optimal environment management. It can increase the productivity and income of SBW breeders in general and be sustainable.